Job Strain as a Risk Factor for Peripheral Artery Disease: A Multi‐Cohort Study. Issue 9 (5th May 2020) - Heikkilä, Katriina; Pentti, Jaana; Madsen, Ida E. H.; Lallukka, Tea; Virtanen, Marianna; Alfredsson, Lars; Bjorner, Jakob; Borritz, Marianne; Brunner, Eric; Burr, Hermann; Ferrie, Jane E.; Knutsson, Anders; et al.
Abstract : Background: Job strain is implicated in many atherosclerotic diseases, but its role in peripheral artery disease (PAD) is unclear. We investigated the association of job strain with hospital records of PAD, using individual‐level data from 11 prospective cohort studies from Finland, Sweden, Denmark, and the United Kingdom. Methods and Results: Job strain (high demands and low control at work) was self‐reported at baseline (1985–2008). PAD records were ascertained from national hospitalization data. We used Cox regression to examine the associations of job strain with PAD in each study, and combined the study‐specific estimates in random effects meta‐analyses. We used τ 2, I 2, and subgroup analyses to examine heterogeneity. Of the 139 132 participants with no previous hospitalization with PAD, 32 489 (23.4%) reported job strain at baseline. During 1 718 132 person‐years at risk (mean follow‐up 12.8 years), 667 individuals had a hospital record of PAD (3.88 per 10 000 person‐years). Job strain was associated with a 1.41‐fold (95% CI, 1.11–1.80) increased average risk of hospitalization with PAD. The study‐specific estimates were moderately heterogeneous (τ 2 =0.0427, I 2 : 26.9%). Despite variation in their magnitude, the estimates were consistent in both sexes, across the socioeconomic hierarchy and by baseline smoking status. Additional adjustment for baseline diabetes mellitus did not change the direction or magnitude of the observed associations. Conclusions: Job strain was associated with small but consistent increase in the risk of hospitalization with PAD, with the relative risks on par with those for coronary heart disease and ischemic stroke.